Public debt in developing Asia: a help or hindrance to growth?. Issue 17 (6th October 2020) - Gunarsa, Singgih; Makin, Tony; Rohde, Nicholas
ABSTRACT: We study the effects of public debt on economic growth using a panel of 25 Asian countries from 1970 to 2015. Using a collection of panel data models, we find weak evidence in favour of a negative relationship. Our estimates imply that a 10% increase in debt predicts declines in growth rates ranging from 0.2% to 0.4%.